Re‐emergence of the Painted Turtle (Chrysemys picta) as a reference species for evo‐devo. Issue 4 (30th June 2014) - Cordero, Gerardo Antonio
SUMMARY Evolutionary developmental biology requires integration of knowledge from multiple levels of organization. Information at the genome level is quickly outpacing crucial descriptive information on developmental processes at the cell, tissue, and organ levels. Unprecedented progress in genomics has enabled the rise of so‐called non‐traditional reference species. However, a substantial, though overlooked, amount of phenotypic information has long been available for species such as the Painted Turtle (Chrysemys picta), which recently became the first turtle to feature a fully sequenced and annotated nuclear genome. In this commentary, I highlight research on the comparative embryology of Chrysemys during the twentieth century and briefly discuss future directions for research on this re‐emerging species for evo‐devo.